Getting to Know Women Convicted of Human Trafficking in Spain: Personal Profiles and Involvement in Crime - Rodríguez-López, Silvia (Women & criminal justice, 2022)
This paper contributes to existing global knowledge on female traffickers by providing data about 43 women punished for human trafficking in Spain between 2015 and 2018. Several factors related to the women’s profiles, methods and roles performed in the criminal enterprise are analyzed, based on information obtained from 39 court judgments. The results highlight the similarity between victims’ and perpetrators’ personal circumstances, and show that women’s involvement in trafficking can vary substantially, illustrating the complex dynamics behind this crime. Overall, the paper underlines the need to develop gender-appropriate policies to prevent human trafficking and guarantee proportionality in criminal justice responses.